MANAJEMEN PEMBELAJARAN BAHASA ARAB DENGAN MENGGUNAKAN GOOGLE CLASSROOM DI SMK MUHAMMADIYAH 01 PALEMBANG - Erni Wahyuningsih; Hellen Tiara (Ihtimam : Jurnal Pendidikan Bahasa Arab, 2021)
This research is qualitative in nature, in which the researcher examines the Muhammadiyah 1 Vocational High School in Palembang. The descriptive method is to describe the phenomena that occur in learning Arabic, namely by using google classroom. The data collection methods used are interviews, documentation and observation. This study aims to determine and understand whether the learning process using google classroom is in accordance with the expected objectives at Muhammadiyah 1 Vocational High School in Palembang which focuses on planning Arabic learning, the process of learning Arabic and evaluating learning Arabic using google classroom.The results of this discussion have been good, seen from the planning of Arabic learning using Google Classroom, it has been well prepared, seeing from the existing RPP and syllabus. it is good according to the existing material. Then the evaluation of Arabic learning using google classroom increases because teachers always provide motivation in the form of prizes so that they have the enthusiasm to learn and carry out the assessment process after carrying out the learning process, namely daily assessments, midterm exams and final semester exams.